Intertextuality in Rhetorical and Critical Heritage Among Arabs - برهم, لطفية; العبدو , زكوان; طحلاوي , خلود (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The Modern Arab critics have stopped at the concepts that we Find in rhetorical and critical heritage among Arabs, and they have occupied with intertextuality, and have divided into two groups: The First of them considers the Arabic heritage as its indicator or seeds For the modern intertextuality the and it makes them great Foundations Western intertextuality theory. The second is of refuses the relation between heritage and intertextuality theory For its difference from. the approved Shapes in rhetorical and critical heritage. In this research, we will stop at some rhetorical and critical issues in the Arabic heritage, to indicate its relation with [intertextuality] as a theory, trying to introduce an integrated vision linking intertextuality with Arabic heritage indicators and indicating its role in improving the term.